Toward a simultaneous description of RAA and v2 for heavy quarks. (January 2016) - Das, S. K.; Scardina, F.; Plumari, S.; Greco, V.
Abstract: The two key observables related to heavy quarks that have been measured in RHIC and LHC energies are the nuclear suppression factor RAA and the elliptic flow v2 . The Simultaneous description of these two observables is a top challenge for all the existing models. We highlight how a consistent combination of four ingredients i.e., the temperature dependence of the energy loss, the full solution of the Boltzmann collision integral for the momentum evolution of heavy quark, the hadronization by coalescence, and the hadronic rescattering, are responsible to address a large part of such a puzzle. We consider four different models to evaluate the temperature dependence of drag coefficients of the heavy quark in the QGP. All these four different models are set to reproduce the same RAA as of the experiments. We show that for the same RAA, the v2 could be quite different depending on the interaction dynamics as well as other ingredients.